Message Passing Based Time Synchronization in Wireless Sensor Networks: A Survey. (26th May 2016) - Sarvghadi, Mohammad Ali; Wan, Tat-Chee
Various protocols have been proposed in the area of wireless sensor networks in order to achieve network-wide time synchronization. A large number of proposed protocols in the literature employ a message passing mechanism to make sensor node clocks tick in unison. In this paper, we first classify Message Passing based Time Synchronization (MPTS) protocols and then analyze them based on different metrics. The classification is based on the following three criteria: structure formation of the network affected by the synchronization protocol, frequency of synchronization process (synchronization interval), and synchronization message overhead. Proposed protocols are analyzed and evaluated from different perspectives based on available data. A comparison table of the reviewed protocols is presented according to the evaluation metrics. Finally, some potential methods will be proposed to improve the synchronization process.